PERAN PROBIOTIK BAKTERI ASAM LAKTAT TERHADAP PRODUKTIVITAS UNGGAS - Sri Sumarsih; B Sulistiyanto; C.I. Sutrisno; E.S Rahayu (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2012)
Probiotics are feed supplements that contain live microbial good bacteria, fungi and yeasts that can be beneficial to the host by improving the microbial balance in the digestive tract. Probiotics have a role in increasing the productivity of poultry through mechanisms: embedded / attached to and colonizes the digestive tract, compete with microbial pathogens by producing an anti microbial pathogens and enhance the host's immune system. This paper will discuss the role of probiotics in improving the productivity of poultry.